SYNTHESIS OF TETRA-SUBSTITUTED IMIDAZOLE DERIVATIVES BY CONDENSATION REACTION USING ZEOLITE H-ZSM 22 AS A HETEROGENEOUS SOLID ACID CATALYST - Bhat, Sami Ullah; Naikoo, Rawoof Ahmad; Mir, Muzzaffar Ahmad; Tomar, Radha (International Journal of Current Pharmaceutical Research, 2016)
Objective: The present work deals with the synthesis of tetrasubstituted imidazoles using environmentally benign and green catalyst H-ZSM-22. Methods: The synthesized catalyst was characterized by FTIR, XRD and the products by FTIR and NMR. Results: H-ZSM-22 has been used as an efficient catalyst for an improved and rapid synthesis of 1,2,4,5 tetrasubstituted imidazoles derivatives using reactants: Benzil, Aldehydes, Amines and Ammonium acetate having excellent yield under solvent conditions. Different derivatives of aldehyde have been used in this reaction. For all the synthesized derivatives, ambient reaction time was found to be of 15-30 min. Conclusion: The main advantage of this reaction is small reaction time, high purity yield, easy work-up and pollution free.